Traces of the first Colombian telenovela and its historical reference with human rights - Serrano Suárez, Over Humberto (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The intended work aims to clarify the theme of the soap opera, the history, the situations of the detention centers and women. For this, from the book by E H Carr What is history? (Carr,1978) there are two citations in mention: